The contribution of C.C. Uhlenbeck to Eskimo-Aleut linguistics - van der Voort, Hein (Études/Inuit/Studies, 2008)
AbstractC.C. Uhlenbeck was a Dutch linguist especially known for his work on comparative Indo-European linguistics, Basque and the Blackfoot Algonquian language. However, he also made some groundbreaking contributions to the comparative linguistic study of the Eskimo-Aleut family. Uhlenbeck was the first to suggest that the Eskimo language family and the Aleut language represent daughter branches of a common ancestor. Also, he was the first who approached the possible relationships between the Eskimo-Aleut language family and the Indo-European, Uralic and Altaic language families in a systematic manner in publications. His work attracted the attention of Eskimologists like Bergsland, Fortescue, Hammerich and Thalbitzer, and it put these long-distance comparative issues on the research agenda. Uhlenbeck never did any fieldwork on Eskimo-Aleut and his work is based entirely on sources written by others. His Eskimo-Aleut work is not generally known, since, being written mainly in Dutch, it is not readily accessible to most Eskimologists.